2012
DOI: 10.1111/j.1365-2052.2012.02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study identifies candidate markers for bull fertility in Holstein dairy cattle

Abstract: The decline in the reproductive efficiency of dairy cattle has become a challenging problem worldwide. Female fertility is now taken into account in breeding goals while generally less attention is given to male fertility. The objective of this study was to perform a genome-wide association study in Holstein bulls to identify genetic variants significantly related to sire conception rate (SCR), a new phenotypic evaluation of bull fertility. The analysis included 1755 sires with SCR data and 38,650 single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 31 publications
2
49
1
Order By: Relevance
“…The data set analyzed by Druet et al (2009) contained only 148 microsatellite markers (ranging from 2 to 10 per chromosome), and none were located on Bos taurus X (BTX), which is known to have an effect on bull fertility (Blaschek et al 2011). Feugang et al (2009) and Peñagaricano et al (2012) used more informative data sets of 10K and 50K SNP chips respectively, but applied relatively simple statistical approaches for detection the association between SNP and semen-quality measures. Only the studies of Blaschek et al (2011) and Fortes et al (2012Fortes et al ( , 2013 showed a combination of dense SNP chips (Illumina BovineSNP50 and Illumina Bovine HD BeadChips; Illumina, San Diego, CA) and robust statistical models.…”
Section: Introductionmentioning
confidence: 99%
“…The data set analyzed by Druet et al (2009) contained only 148 microsatellite markers (ranging from 2 to 10 per chromosome), and none were located on Bos taurus X (BTX), which is known to have an effect on bull fertility (Blaschek et al 2011). Feugang et al (2009) and Peñagaricano et al (2012) used more informative data sets of 10K and 50K SNP chips respectively, but applied relatively simple statistical approaches for detection the association between SNP and semen-quality measures. Only the studies of Blaschek et al (2011) and Fortes et al (2012Fortes et al ( , 2013 showed a combination of dense SNP chips (Illumina BovineSNP50 and Illumina Bovine HD BeadChips; Illumina, San Diego, CA) and robust statistical models.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a region with effects on both production and fertility traits was reported on chromosome 5 [52,79,111,119,132]. The significant variants identified in this region (at 87-100 Mb on chromosome 5) were reported to be associated with C22:1 milk fatty acid content, milk fat yield [52,132], protein yield [28], calving to first service interval [111] and sire conception rate in Angus, Brown Swiss and Holstein cattle [60,117]. Several candidate genes were reported within this region including ST8SIA1, ABCC9, GABARAPL1 and SLO1C1 [111,119].…”
Section: Genomic Regions and Genes Affecting Multiple Traits In Dairymentioning
confidence: 99%
“…Most of the reports have highlighted the most significant SNPs, but varied results have been obtained. Several SNPs exhibiting significant associations with poor sperm motility, sperm concentration, bull fertility and fertilizing ability of sperm, and subsequent embryonic development were found; however, detailed SNP information was not provided [2][3][4][5]. Therefore, candidate gene approaches have been applied to detect variations or polymorphisms existing among individuals in a bull population to detect specific DNA regions and to increase selection efficiency, particularly in low-heritability sperm quality traits.…”
Section: Introductionmentioning
confidence: 96%
“…With advancements in genetic and molecular techniques, DNA polymorphisms have been applied in marker-assisted selection of animals. Several studies have investigated single-nucleotide polymorphism (SNP) associations with sperm quality traits by genome-wide association analyses in various cattle populations [2][3][4]. Most of the reports have highlighted the most significant SNPs, but varied results have been obtained.…”
Section: Introductionmentioning
confidence: 97%